MASTERBATCH, AROMATIC POLYESTER RESIN COMPOSITION, MOLDED ARTICLE AND METHOD FOR PRODUCTION THEREOF
Patent Information
- Application Number
- JP2020190800
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-17
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-11-17
Smart Images

Figure 0007639305000001 
Figure 0007639305000002 
Figure 0007639305000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a masterbatch containing polybutylene terephthalate (hereinafter also referred to as "PBT"), a resin composition containing an aromatic polyester, a molded article, and a method for producing them. More specifically, the present invention relates to a method for producing an aromatic polyester resin composition for film, a masterbatch used therein and a method for producing the masterbatch, and a method for producing a film using the aromatic polyester resin composition for film. [Background technology]
[0002] PBT resin is widely used for a variety of purposes due to its excellent properties, including ease of molding, mechanical properties, heat resistance, and chemical resistance. In recent years, it has also begun to be used for films and sheets, taking advantage of its gas barrier properties.
[0003] However, this film has low slipperiness, and when wound up into a roll, the films stick to each other, making it difficult to pull out the film, and there are problems in that scratches and wrinkles are formed when the film is pulled out forcefully.
[0004] For this reason, a method has been adopted in which fine particles are added to form unevenness on the film surface to increase the slipperiness of the film (see Reference 1). However, the use of fine particles increases the tendency for poor dispersion to occur, particularly in the master batch where the fine particles are highly concentrated, which not only leads to the occurrence of film defects and an increase in filter pressure during film production, but also accelerates resin degradation, making stable film production difficult. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-81825 A Summary of the Invention [Problem to be solved by the invention]
[0006] The problem that the present invention aims to solve is to provide an aromatic polyester resin composition and a method for producing the same, which are films made of an aromatic polyester resin composition containing at least a PBT resin, and which suppress the occurrence of film defects, suppress filter pressure rise when producing a film from the resin composition, and further suppress the progression of resin deterioration, enabling stable film production; and to provide a masterbatch and a method for producing the same that can provide such an aromatic polyester resin composition for films. [Means for solving the problem]
[0007] In order to solve the above problems, the inventors conducted extensive research and discovered that by optimizing the ratio of fine particles in a masterbatch, particle aggregation, which is a defect in films produced using the masterbatch, can be eliminated and resin deterioration, which causes deterioration of film formability, can be suppressed, thereby solving the present invention.
[0008] That is, the present invention provides the following inventions. [1] The present invention relates to a master batch (1) characterized by containing, per 100 parts by mass of a polybutylene terephthalate resin (a) having an intrinsic viscosity of 0.9 to 1.5, 1 part by mass or more and less than 5 parts by mass of fine particles (b) having an average particle size of 0.5 to 10 μm.
[0009] [2] The present invention also relates to a method for producing a masterbatch, comprising the step of blending and melt-kneading 100 parts by mass of polybutylene terephthalate resin (a) having an intrinsic viscosity of 0.9 to 1.5 with 1 part by mass or more and less than 5 parts by mass of fine particles (b) having an average particle size of 0.5 to 10 μm.
[0010] [3] The present invention further provides a method for producing a polybutylene terephthalate resin composition exclusively used for films, comprising: The present invention relates to a method for producing an aromatic polyester polybutylene terephthalate resin composition, comprising a step of blending an aromatic polyester polybutylene terephthalate resin (c) with the masterbatch described in [1] and melt-kneading the blend.
[0011] [4] The present invention further relates to a method for producing a film, comprising a step of melt-molding the aromatic polyester polybutylene terephthalate resin composition obtained by the production method described in [3].
[0012] [5] The present invention further relates to a method for producing a film, comprising the steps of blending an aromatic polyester polybutylene terephthalate resin (c) with the masterbatch described in [1], melt-kneading the blend, and melt-molding the blend. Effect of the Invention
[0013] According to the present invention, there are provided a film made of an aromatic polyester resin composition containing at least a PBT resin, which suppresses the occurrence of film defects, suppresses filter pressure rise when forming a film from the resin composition, and further suppresses the progression of resin deterioration, enabling stable film formation, as well as a method for producing the aromatic polyester resin composition and a film; and a masterbatch and a method for producing the same that can provide such an aromatic polyester resin composition for films. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to the following embodiments.
[0015] <Master batch> The master batch of this embodiment is characterized by containing 1 part by mass or more and less than 5 parts by mass of fine particles (b) having an average particle size of 0.5 to 10 μm per 100 parts by mass of polybutylene terephthalate resin (a) having an intrinsic viscosity of 0.9 to 1.5. The method for producing the masterbatch of this embodiment is characterized by comprising a step of blending and melt-kneading 100 parts by mass of polybutylene terephthalate resin (a) having an intrinsic viscosity of 0.9 or more and 1.5 or less with 1 part by mass or more and less than 5 parts by mass of fine particles (b) having an average particle size of 0.5 to 10 μm.
[0016] [PBT resin (a)] The PBT resin (a) used in the present invention has an intrinsic viscosity of 0.9 or more, preferably 1.0 or more, and 1.5 or less, preferably 1.4 or less, because this eliminates particle aggregation that causes film defects and suppresses resin deterioration that causes deterioration of film formability during film production.
[0017] The PBT resin used in the present invention has a structure in which terephthalic acid units and 1,4-butanediol (hereinafter sometimes abbreviated as BG) units are ester-bonded, and is a polymer in which 50 mol % or more of the dicarboxylic acid units are composed of terephthalic acid units and 50 mol % or more of the diol component are composed of BG units.
[0018] Here, the proportion of terephthalic acid units in all dicarboxylic acid units is preferably 70 mol% or more, more preferably 80 mol% or more, and particularly preferably 95 mol% or more, and the proportion of BG units in all diol units is preferably 70 mol% or more, more preferably 80 mol% or more, and particularly preferably 95 mol% or more.
[0019] In the present invention, the dicarboxylic acid component other than terephthalic acid is not particularly limited, and examples thereof include aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, 4,4'-benzophenonedicarboxylic acid, 4,4'-diphenoxyethanedicarboxylic acid, 4,4'-diphenylsulfonedicarboxylic acid, and 2,6-naphthalenedicarboxylic acid, alicyclic dicarboxylic acids such as 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid, and aliphatic dicarboxylic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid. These dicarboxylic acid components can be introduced into the polymer skeleton as dicarboxylic acids or using dicarboxylic acid derivatives such as dicarboxylic acid esters and dicarboxylic acid halides as raw materials.
[0020] In the present invention, the diol component other than BG is not particularly limited, and examples thereof include aliphatic diols such as ethylene glycol, diethylene glycol, polyethylene glycol, 1,2-propanediol, 1,3-propanediol, polypropylene glycol, polytetramethylene glycol, dibutylene glycol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, and 1,8-octanediol; alicyclic diols such as 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,1-cyclohexanedimethylol, and 1,4-cyclohexanedimethylol; and aromatic diols such as xylylene glycol, 4,4'-dihydroxybiphenyl, 2,2-bis(4-hydroxyphenyl)propane, and bis(4-hydroxyphenyl)sulfone.
[0021] [Fine particles (b)] The fine particles (b) used in the present invention have an average particle size of 0.5 μm or more, preferably 1.0 μm or more from the viewpoint of slipperiness, and 10 μm or less, and 8.0 μm or less from the viewpoint of transparency. The fine particles used in the present invention are not particularly limited, but include, for example, silicates such as wollastonite, sericite, kaolin, mica, clay, bentonite, asbestos, talc, and alumina silicate, metal oxides such as alumina, silicon chloride, magnesium oxide, zirconium oxide, and titanium oxide, carbonates such as calcium carbonate, magnesium carbonate, and dolomite, sulfates such as calcium sulfate and barium sulfate, glass beads, boron nitride, silicon carbide, and inorganic fine particles such as silica, which may be hollow. One or more of these may be used in combination. Among these, silica and alumina silicate are preferred from the viewpoint of imparting slipperiness to the film and being more transparent.
[0022] In addition, the surface of the fine particles used in the present invention may be hydrophobic or hydrophilic, but it is more preferable that the surface is hydrophilic, since the transparency of the film finally obtained is further improved. The hydrophobic or hydrophilic surface of the fine particles used in the present invention can be made hydrophobic or hydrophilic by carrying out a known hydrophobic or hydrophilic treatment as necessary, and if the fine particles themselves have the desired hydrophobic or hydrophilic property, they can be used without treatment.
[0023] The degree of hydrophobicity or hydrophilicity of the surface of the microparticles used in the present invention can be expressed, for example, by the DBA adsorption amount, and in the case of hydrophobicity, the DBA adsorption amount is preferably in the range of less than 300 meq / kg, while in the case of hydrophilicity, the DBA adsorption amount is preferably in the range of 400 meq / kg or more. However, the DBA adsorption amount can be measured by the method in the Examples.
[0024] Examples of fine particles that can be suitably used in the present invention include the "SYLOPHOBIC" series of silica (silicon dioxide) fine particles manufactured by Fuji Silysia Chemical Ltd., which are fine particles having a hydrophobic surface, while the "SYLYSIA" series of silicon dioxide fine particles manufactured by Fuji Silysia Chemical Ltd., the "SEAHOSTAR" series of silica fine particles manufactured by Nippon Shokubai Co., Ltd., and the "SILTON" series of alumina silicate (aluminosilicate) fine particles manufactured by Mizusawa Industrial Chemical Co., Ltd., are examples of fine particles having a hydrophilic surface.
[0025] The ratio of the PBT resin (a) to the microparticles (b) in the masterbatch is in the range of less than 5 parts by mass, preferably 4.5 parts by mass or less, and more preferably 4 parts by mass or less of the microparticles (b) per 100 parts by mass of the PBT resin (a), from the viewpoint of eliminating particle aggregation and preventing deterioration of film-forming properties. The lower limit is not limited, but from the viewpoint of efficiency as a masterbatch, it is preferably 1 part by mass or more, more preferably 1.5 parts by mass or more, and even more preferably 2 parts by mass or more.
[0026] [Other ingredients] The master batch may contain other components as optional components in addition to the essential components of the PBT resin (a) and the fine particles (b) within the scope of the gist of its function. Specific examples of other components include antioxidants, ultraviolet absorbers, colorants, pigments, dyes, foaming agents, lubricants, flame retardants, and fillers. When other components are used as optional components, their blending ratio is not particularly limited as long as it does not impair the effects of the present invention, but it is preferable to use them in a range of 50 parts by mass or less, and more preferably 25 parts by mass or less, relative to 100 parts by mass of the PBT resin (a). By adjusting the types and amounts of these components, the desired functions can be freely adjusted.
[0027] <Masterbatch manufacturing method> The method for producing a masterbatch of the present invention includes a step of blending and melt-kneading the PBT resin (a) and the fine particles (b) (hereinafter, sometimes referred to as "step (1)").
[0028] First, the essential components of the PBT resin (a) and the fine particles (b) and, if necessary, the other components as optional raw material components are mixed in various forms such as bulk, pellets, chips, etc., to a predetermined mixing ratio, and then, after premixing as necessary, they are put into a melt kneader and heated to the melting point of the PBT resin (a) or higher to melt-knead. The form of the melt kneaded product is not particularly limited as long as it does not impair the effects of the present invention, and it can be made into the thermoplastic resin composition or molded product of the present invention by directly adding a diluent resin described later in the molten state, but it is preferable to extrude it into a strand shape and then cut it into granular shapes such as pellets and chips.
[0029] In the step (1), the premixing is not particularly limited as long as it does not impair the effects of the present invention, and examples of the premixing include dry blending using a ribbon blender, a Henschel mixer, a V-blender, etc. Furthermore, the melt kneader is not particularly limited as long as it does not impair the effects of the present invention, and examples of the melt kneader include a Banbury mixer, a mixing roll, a single-screw or twin-screw extruder, and a melt kneader equipped with a heating mechanism, such as a kneader. The melt kneader in the above step may be equipped with a filter having an opening of preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 30 μm or less.
[0030] The intrinsic viscosity of the thus obtained masterbatch of the present invention is not particularly limited, but is preferably 0.6 or more and preferably 0.9 or less.
[0031] <Aromatic polyester resin composition and molded article (film) thereof> The method for producing the aromatic polyester resin composition and the molded article (film) of the present invention includes a step of blending and melt-kneading the master batch and the aromatic polyester resin (c) as a diluting resin (hereinafter, sometimes referred to as "step (2)"). The aromatic polyester resin composition or the molded article is a cured product (a product that is softened and flowed by heating and solidified by cooling) of the blend of the master batch and the aromatic polyester resin (c). The aromatic polyester resin composition is not particularly limited, but it is, for example, an intermediate molded product when obtaining a film from the master batch, and means a material having a predetermined form such as pellets or powder.
[0032] [Aromatic polyester resin (c)] The aromatic polyester resin (c) used in the present invention is used as a diluting resin for the master batch. The aromatic polyester resin (c) used in the present invention is not particularly limited, but examples thereof include polyethylene terephthalate (PET), polypropylene terephthalate, polybutylene terephthalate (PBT), polyhexylene terephthalate, polycyclohexylene dimethylene terephthalate (PCT), polytrimethylene terephthalate (PTT), polyethylene naphthalate (PEN), polybutylene naphthalate (PBN), polycyclohexane dimethyl phthalate (PCN), polytrimethylene naphthalate (PTN), amorphous polyester resin (PETG, PCTG), polyethylene-1,2-bis(phenoxy)ethane-4,4'-dicarboxylate, polyethylene isophthalate / terephthalate, polybutylene terephthalate / isophthalate, etc. In addition, one type selected from these polyester resins may be used alone, or two or more types may be used in combination.
[0033] Among these, the aromatic polyester resin (c) can be the same as the PBT resin (a) listed above. When the PBT resin (c) is the same as the PBT resin (a) listed above, it may be the same as or different from the PBT resin (a) contained in the master batch, but it is preferable to use the same type of resin from the viewpoint of compatibility.
[0034] The blending ratio of the master batch to the aromatic polyester resin (c) may be appropriately adjusted so that the content of the microparticles (b) is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, and preferably 3 mass% or less, more preferably 1.5 mass% or less, and even more preferably 1 mass% or less, when the total mass of the master batch and the aromatic polyester resin (c) in the aromatic polyester resin composition or film is taken as 100 mass%. [Other ingredients] The aromatic polyester resin composition or film may contain other components as optional components in addition to the essential components of the master batch and aromatic polyester resin (c) within the scope of the essential function. Specific examples of other components include antioxidants, ultraviolet absorbers, colorants, pigments, dyes, foaming agents, lubricants, flame retardants, and fillers.
[0035] <Method of producing aromatic polyester resin composition and film> In the method for producing an aromatic polyester resin composition or film according to the present embodiment, the essential components of the masterbatch and aromatic polyester resin (c) obtained by the above-mentioned production method, and other optional components as necessary, are mixed in various forms such as bulk, pellets, and chips to a predetermined mixing ratio, and then premixed as necessary, and then put into a melt kneader and heated to the melting point of the higher of the PBT resin (a) or the aromatic polyester resin (c) or higher to melt knead. This allows the film to be directly melt molded, but it is also possible to obtain the desired film by first going through a process of obtaining a pellet-shaped or powdered aromatic polyester resin composition and then melt molding the obtained pellet-shaped or powdered aromatic polyester resin composition. By obtaining a film via the masterbatch in this way, the fine particles can be more stably and uniformly dispersed in the film, and the desired functions and properties of the fine particles can be sufficiently imparted to the film. In addition, by forming a film via the masterbatch, hydrolysis of the aromatic polyester resin is significantly suppressed, and the moldability (processability), mechanical properties, and appearance quality can be improved.
[0036] When the thermoplastic resin composition of the present invention is made into a film, the molten resin can be extruded (squeezed) from a slit-shaped hole after melt kneading to form a film or sheet. The film or sheet-shaped thermoplastic resin molded product (film) may be further molded by a press molding method or a vacuum molding method, or may be formed on a base layer to form a multilayer film. In the present invention, the term "film" refers to a film- or sheet-shaped thermoplastic resin molded product, and is a general term that does not strictly distinguish between plate-shaped products such as films and sheets. In the present invention, the thickness of the film varies depending on the application and can be any thickness, but is usually in the range of preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, particularly preferably 0.3 μm or more, and most preferably 0.5 μm or more, to preferably 1 mm or less, more preferably 500 μm or less, even more preferably 150 μm or less, particularly preferably 100 μm or less, and most preferably 70 μm or less. EXAMPLES
[0037] Examples of the present invention will be described below. The present invention is not limited to the following examples. In the examples, unless otherwise specified, "parts" indicates mass% and the units of the numerical values in the tables are parts by mass.
[0038] (Measurement example) Intrinsic viscosity The intrinsic viscosity of the PBT resin was measured by dissolving the PBT resin in an octochlorophenol solution at a temperature of 23°C.
[0039] (Measurement example) DBA adsorption amount Weigh out 250mg of dried sample, add 50ml of N / 500-di-n-butylamine solution (petroleum benzine solvent) and leave at 20℃ for about 2 hours. Add 5ml of chloroform and 2-3 drops of indicator (crystal violet) to 25ml of this supernatant, and titrate with N / 100-perchloric acid solution (acetic anhydride solvent) until the purple color changes to blue. The titration value at this point is taken as Aml. A separate blank was run and taken as Bml, and the DBA adsorption amount was calculated using the following formula.
[0040]
number
[0041] (Measurement example) Resin deterioration (intrinsic viscosity retention rate) The retention rate of intrinsic viscosity was calculated to evaluate the state of resin deterioration. The closer the retention rate is to 100%, the better the resin deterioration is suppressed.
[0042]
number
[0043] (Measurement example) Increase in filtration pressure of master batch (MB) The differential pressure (increase in filtration pressure) was measured when 1 kg of the master batch was passed through a single-screw extruder equipped with a filter with a 20 μm mesh, and the particle coagulation was evaluated according to the following criteria. Note that a larger differential pressure indicates a larger amount of coagulated particles. ◎ Less than 0.5MPa ○ 0.5MPa or more and less than 2MPa △ 2MPa or more and less than 5MPa × 5MPa or more
[0044] (Measurement example) Agglomerated particles in film The film was observed under an optical microscope at 100 cm 2 The amount of agglomerated particles of 15 μm or more present per unit area was evaluated according to the following criteria. ◎ Less than 5 ○ 5 or more but less than 10 △ 10 or more but less than 20 ×...20 or more
[0045] (Measurement example) Film formability The stability during film formation was evaluated according to the following criteria. ○ The state of the discharged material is stable, and film production is completed without any problems. △: Viscosity decrease of the discharged material, pulsation phenomenon, fluctuation in discharge width, foaming, etc. were observed, but film production was completed. ×... A stable film cannot be obtained due to a decrease in viscosity of the discharged material, pulsation phenomenon, fluctuation in discharge width, foaming, etc.
[0046] Examples 1 to 4 and Comparative Examples 1 to 3 (Production of Masterbatches) PBT resin and fine particles were mixed in the mixing ratio shown in Table 1 and dry blended, and then melt-kneaded in a 30 mmφ twin-screw extruder (set temperature 260°C). The resulting composition was pelletized to obtain a master batch.
[0047] [Table 1]
[0048] [Table 2]
[0049] The values in the table are based on mass, and the following components were used. PBT-1: Polyplastics PBT resin "DURANEX 600FP" (intrinsic viscosity 1.0 dl / g) PBT-2: Polyplastics PBT resin "DURANEX 800FP" (intrinsic viscosity 1.4 dl / g) FP-1: Silica microparticles (Fuji Silysia Chemical's SYLYSIA® 550, average particle size 3.9 μm, DBA adsorption capacity 800 meq / kg) FP-2 Aluminosilicate fine particles (Mizusawa Chemical Industry Co., Ltd. "SILTON (registered trademark) JC-50", average particle size 4.9 μm) FP-3: Silica fine particles (Fuji Silysia Chemical's SYLOPHOBIC (registered trademark) 505, average particle size 3.9 μm, DBA adsorption capacity 175 meq / kg)
[0050] Examples 5 to 8 and Comparative Examples 4 to 6 (Film Production) A predetermined amount of PBT resin (Polyplastics' "DURANEX 300FP", intrinsic viscosity 0.7) and master batches (MB(1)-(4), MB(c1)-(c2)) were mixed so that the fine particle concentration in the film was 0.3 wt%, and dried at 120°C for 12 hours. Next, using an extruder connected to a 100 mm wide T-die, a film was formed at a film formation temperature of 260°C, and a film with a thickness of 30 μm was obtained. The obtained film was subjected to various measurements and the results are shown in Tables 3 and 4.
[0051] [Table 3]
[0052] [Table 4]
[0053] It was found that the films of Examples 5 to 8 obtained via the masterbatches produced in Examples 1 to 4 had an optimal concentration of fine particles in the masterbatches, which eliminated particle aggregation that is a defect in the films, and suppressed resin deterioration that causes deterioration of film formability during film production. On the other hand, the films of Comparative Examples 4 to 6 obtained via the masterbatches produced in Comparative Examples 1 to 3 could not eliminate particle aggregation in the masterbatches, which resulted in the occurrence of film defects and an increase in filter pressure during film production. It was also revealed that film production was reduced during film production due to the progression of resin deterioration.
Claims
1. The composition contains 1 part by mass or more and less than 5 parts by mass of fine particles (b) having an average particle size of 0.5 to 10 μm per 100 parts by mass of a polybutylene terephthalate resin (a) having an intrinsic viscosity of 0.9 to 1.5, The master batch is characterized in that the fine particles (b) have a hydrophilic surface and have a DBA adsorption amount of 400 meq / kg or more.
2. A method for producing a masterbatch, comprising the steps of blending and melt-kneading 100 parts by mass of polybutylene terephthalate resin (a) having an intrinsic viscosity of 0.9 to 1.5 with 1 part by mass to less than 5 parts by mass of fine particles (b) having a hydrophilic surface and an average particle size of 0.5 to 10 μm and a DBA adsorption amount of 400 meq / kg or more.
3. A method for producing an aromatic polyester resin composition exclusively used for films, comprising the steps of: A method for producing an aromatic polyester resin composition, comprising the step of blending an aromatic polyester (c) with the masterbatch according to claim 1 and melt-kneading the blend.
4. A method for producing a film, comprising a step of melt-molding the aromatic polyester resin composition obtained by the method according to claim 3.
5. A method for producing a film, comprising the steps of blending an aromatic polyester resin (c) with the masterbatch according to claim 1 and melt-kneading the blend, and melt-molding the blend.
6. The masterbatch described in claim 1, characterized in that the microparticles (b) are silica.
7. A method for producing a masterbatch as described in claim 2, characterized in that the microparticles (b) are silica.
8. A method for producing a masterbatch as described in claim 2, characterized in that after the melt-kneading process, the masterbatch is granulated.
9. A method for producing an aromatic polyester resin composition as described in claim 3, characterized in that the content of the microparticles (b) is 0.01 mass% or more and 3 mass% or less when the total mass of the master batch and the aromatic polyester resin (c) is 100 mass%.
Citation Information
Patent Citations
Sheet or film excellent in transparency and tearability
JP2004244555A
Polyester film, complex of the film and metal foil, and formation made by putting sealant layer on the complex
JP2015131888A
Polybutylene terephthalate resin master batch for film, and polybutylene terephthalate resin composition for film
JP2019081825A
Resin additive composition and resin composition
WO2007000876A1
Polyester film, laminate produced using said film, and structure comprising said laminate and sealant layer
WO2014069236A1